Social and Environmental Education: A Review of Research and Scholarship in Geography, History and Education about Religions and Beliefs in the Context of the Redeveloped Irish Primary School Curriculum - (:unkn) unknown (National Council for Curriculum and Assessment, 2023)
It is evident that the subjects of SEE provide opportunities for children to be active and agentic in their learning, with a sense of responsibility to participate in the world. SEE creates spaces for children to be creative and to question both the world around them, and more distant times and places. Within SEE, children have the opportunity to enquire and to think in a variety of ways while discovering patterns, collecting and analysing a range of data and using a range of resources. Through the signature pedagogies and processes within SEE, children also have the opportunity to develop their digital skills. For their current and future lives, SEE enables children to live well through gaining a sense of space, place and time as well as acquiring new knowledge and skills to enable them to negotiate and shape the world around them. The importance of teachers having a strong knowledge of the discipline, expertise in cross-curricular teaching, and subject-specific pedagogical content knowledge is emphasised across the report. The proposed areas and subjects of SEE align with the vision and principles of the Primary Curriculum Framework and there is significant potential for SEE to make an important contribution to the framework itself.
Keywords: Digital Humanities; Inclusive Society; Smart & Sustainable Planet; Curriculum reform in primary and post-primary education; Education about Religion and Beliefs; Environmental Education; Geography Education; History Education; Primary education; Social Education